2017
DOI: 10.1002/cpt.792
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: Treatment Progress and Limitations

Abstract: There is an increasing understanding on the etiology of chronic immune-mediated inflammatory diseases such as inflammatory bowel disease (IBD), psoriasis, or rheumatoid arthritis. Large consortia contributed to the elucidation of the genetics, for instance, of IBD identifying a number of genes involved in innate mucosal defense and immune tolerance (most prominent, e.g., NOD2) and other related processes. For a number of such diseases, common genetic susceptibility loci were identified, suggesting overlapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Best clinical outcome with fewer drug-related adverse reactions result in improved patient outcomes and optimal resource utilization; these goals are at the heart of personalized medicine. Research in patient-centered therapies based on the understanding of disease pathogenesis, genetic susceptibility, and inter-individual variability to treatment is ongoing (58,59). The importance of personalized treatment in children is indicated by recent studies in childhood-onset CD, which have shown that non-sustained response to treatment may be more important in predicting disease relapse and overall complications than actual disease severity and extent at diagnosis (60).…”
Section: Discussionmentioning
confidence: 99%
“…Best clinical outcome with fewer drug-related adverse reactions result in improved patient outcomes and optimal resource utilization; these goals are at the heart of personalized medicine. Research in patient-centered therapies based on the understanding of disease pathogenesis, genetic susceptibility, and inter-individual variability to treatment is ongoing (58,59). The importance of personalized treatment in children is indicated by recent studies in childhood-onset CD, which have shown that non-sustained response to treatment may be more important in predicting disease relapse and overall complications than actual disease severity and extent at diagnosis (60).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids, mesalamine, and immunosuppressive medicines, which are currently utilized to treat UC, are linked with serious adverse effects and do not give long-term cures [ 14 ]. Natural products are promising alternatives to conventional therapy for the UC treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 The drugs currently used to treat IBD are often associated with side effects, and these medications do not provide long-term relief or cures for IBD. 5 Consequently, there is an urgent need to uncover more effective treatments for IBD. Altered expression of glycosidases and glycosyltransferases and dysbiosis of the intestinal flora can disrupt the mucus layer, polysaccharideagglutinin interactions, and host-flora interactions, ultimately leading to IBD.…”
Section: Introductionmentioning
confidence: 99%